PENINGKATAN HASIL BELAJAR IPS SISWA MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES DI KELAS V SD - Musdalifa, Eva; Suherman, Farida; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study is aimed to improve learning outcomes of Social science by using the model of Examples Non Examples in the fifth grade of elementary school. Types of this research was classroom action research with qualitative and quantitative approaches. The research subjects were 28 students from the fifth grade of elementary school consist of 17 boys and 11 girls. The implementation is done in two cycles with the research procedure consist of planning, implementation, observation, and reflection. The result showed an increase a) lesson plant the cycles of the cycles I was 82,14% and the cycles II was 92,85%, b) the implementation of the aspect of the teacher in the cycles I was 82,5% and the cycles II was 95%, while the implementation of the aspect of the student in the cyvles I was 80% and the cycles II 95%, c) students learning outcomes cycles I was 73,2 and cycles II was 86,3. The conclusion of the study using Example Non Example can improve the study outcomes of social science in the fifth grade of elementary school in SDN 07 Nan Sabaris. Keywords: Study Outcomes; Learning Social Science; Examples Non Examples